COVID-19 im Alter – Die geriatrische Perspektive - Wirth, Rainer; Becker, C.; Djukic, M.; Drebenstedt, C.; Heppner, Hans Jürgen; Jacobs, A. H.; Meisel, M.; Michels, G.; Nau, Roland; Pantel, J.; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2021)
Predominantly the older population is affected by a severe course of COVID-19. The mortality of hospitalized patients with COVID-19 above the age of 80 years is up to 54% in international studies. These observations indicate the necessity to highlight the geriatric perspective on this disease. The diagnostics and treatment of COVID-19 do not differ between younger and older patients but atypical symptoms should be expected more frequently in old age. Older subjects show an increased need for rehabilitation after COVID-19. Paradoxically, increasing rehabilitation demands go along with a reduced availability of geriatric rehabilitation options, the latter being a consequence of closure or downsizing of rehabilitation departments during the pandemic. In general, measures of isolation and quarantine should be diligently balanced as the health and emotional consequences of such measures may be severe in older persons. In light of the poor prognosis of older COVID-19 patients, advanced care planning becomes even more relevant. Caregivers and physicians should be encouraged to compose advanced care directives that also reflect the specific circumstances of COVID-19. Fortunately, current data suggest that the effectiveness of the vaccination with the mRNA-vaccines approved in Germany may be equally high in older compared to younger persons.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Aging; Geriatrics; Pandemia; Rehabilitation; SARS-CoV-2